-4-8(6z+4)=8(4z-7)-1

Simple and best practice solution for -4-8(6z+4)=8(4z-7)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-8(6z+4)=8(4z-7)-1 equation:


Simplifying
-4 + -8(6z + 4) = 8(4z + -7) + -1

Reorder the terms:
-4 + -8(4 + 6z) = 8(4z + -7) + -1
-4 + (4 * -8 + 6z * -8) = 8(4z + -7) + -1
-4 + (-32 + -48z) = 8(4z + -7) + -1

Combine like terms: -4 + -32 = -36
-36 + -48z = 8(4z + -7) + -1

Reorder the terms:
-36 + -48z = 8(-7 + 4z) + -1
-36 + -48z = (-7 * 8 + 4z * 8) + -1
-36 + -48z = (-56 + 32z) + -1

Reorder the terms:
-36 + -48z = -56 + -1 + 32z

Combine like terms: -56 + -1 = -57
-36 + -48z = -57 + 32z

Solving
-36 + -48z = -57 + 32z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-32z' to each side of the equation.
-36 + -48z + -32z = -57 + 32z + -32z

Combine like terms: -48z + -32z = -80z
-36 + -80z = -57 + 32z + -32z

Combine like terms: 32z + -32z = 0
-36 + -80z = -57 + 0
-36 + -80z = -57

Add '36' to each side of the equation.
-36 + 36 + -80z = -57 + 36

Combine like terms: -36 + 36 = 0
0 + -80z = -57 + 36
-80z = -57 + 36

Combine like terms: -57 + 36 = -21
-80z = -21

Divide each side by '-80'.
z = 0.2625

Simplifying
z = 0.2625

See similar equations:

| 7r=-1/2 | | f(2+a)=5(2+a)-7 | | h+19/19=2 | | 3=-7 | | 950+700+4x=850+200+9x | | f(4)=5(4)-7 | | +5=1+k | | 11-4x=0.5 | | 19+-5p=-1 | | (3/5)w-(1/7)=(-3/7)w+(3/7) | | 7r=-7 | | 12-(1/26)(2x)=6-(1/26)(x) | | 7x*8k=8x-17k | | 5x+2/7x-6 | | 4y^2-5y^2+7y^2= | | [SQRT(x+3)]=2[SQRT(x)] | | x^3+2x^2-6x=12 | | (5/4)y-(3/8)=(7/2)y+(3/8) | | 0.1=.07+x(0.12) | | 2(x/3-3)=16 | | 3(3n-3)=-54 | | (9x-3)*(-0.7)= | | 6+9z=7 | | -6v+11=-4v+1 | | (-5i)+(I)= | | 2x^2+58=20x | | (-7)(8)-(-6)(-2)= | | 6x^2+2x-17=0 | | 1.5z=z | | 8x+10+2x=90 | | (1/x)+(1/x+3)=(1/4) | | -9z-9=-4z+6 |

Equations solver categories